Chronic Placental Inflammation in Twin Pregnancies - Heejin Bang; Go Eun Bae; Ha Young Park; Yeon Mee Kim; Suk-Joo Choi; Soo-young Oh; Cheong-Rae Roh; Jung-Sun Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Chronic placental inflammation, such as villitis of unknown etiology (VUE) and chronic chorioamnionitis (CCA), is considered a placental manifestation of maternal anti-fetal rejection. The aim of this study is to investigate its frequency in twin pregnancies compared to singleton pregnancies. Methods: Three hundred twin placentas and 1,270 singleton placentas were consecutively collected at a tertiary medical center in Seoul, Republic of Korea from 2009 to 2012. Hematoxylin and eosin sections of tissue samples (full-thickness placental disc and chorioamniotic membranes) were reviewed. Results: Non-basal VUE was more frequent in twin placentas than in singleton placentas (6.0% vs 3.2%, p < .05). In preterm birth, CCA was found less frequently in twin placentas than in singleton placentas (9.6% vs 14.8%, p < .05), reaching its peak at an earlier gestational age in twin placentas (29-32 weeks) than in singleton placentas (33-36 weeks). CCA was more frequent in twin pregnancies with babies of a different sex than with those with the same sex (13.8% vs 6.9%, p=.052). Separate dichorionic diamniotic twin placentas were affected by chronic deciduitis more frequently than singleton placentas (16.9% vs 9.7%, p<.05). Conclusions: The higher frequency of non-basal VUE in twin placentas and of CCA in twin placentas with different fetal sex supports the hypothesis that the underlying pathophysiological mechanism is maternal anti-fetal rejection related to increased fetal antigens in twin pregnancies. The peak of CCA at an earlier gestational age in twin placentas than in singleton placentas suggests that CCA is influenced by placental maturation.